CLINICAL AND EPIDEMIOLOGICAL ASSESSMENT OF THE EFFECTIVENESS OF VACCINATION OF CHILDREN AGAINST PNEUMOCOCCAL INFECTION IN THE AMUR REGION - A. G. Chuchalin; G. G. Onischenko; V. P. Kolosov; O. P. Kurganova; N. L. Tezikov; L. G. Manakov; Yu. M. Perelman (Журнал микробиологии, эпидемиологии и иммунобиологии, 2016)
Aim. To study the effectiveness of anti-pneumococcal vaccination of children in the organization of anti-epidemic measures in the areas of the flood in the Amur region. Material and methods. The monitoring program included 4988 children aged 2 to 5 years who have risk factors for pneumococcal infection. Pneumococcal conjugate vaccine Prevenar-13 was used for immunization. Data on the incidence of child with acute respiratory infection, acute otitis media, pneumonia, meningitis during the post-vaccination period were taken into account. To evaluate the effectiveness of vaccination we used indicators and specific criteria (coefficient prophylactic vaccination and infection index). Results. The level of total morbidity of children in post-immunization period decreased by 13.6%; the number of cases of pneumonia in the population of observed children decreased by 2.3 times; the total duration of the illness in children decreased by 14.6%, the number of courses of antibiotic therapy was reduced by 21.3%, the number of hospital admissions of children- 38.4%, the number of days of temporary disability of parents - 11.1%. Direct dependence of the degree of effectiveness of vaccination against pneumococcal disease by the age of children is determined. Conclusion. The findings suggest that implementation of the program of clinical and epidemiological monitoring and prevention of community-acquired pneumonia with use of a vaccine against pneumococcal infections in the territory of the Amur Region has a high level of medical and socio-economic efficiency.